(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To assess the level of Cathepsin D in the selected chemotherapeutic regimens used for breast cancer and to compare the effectiveness of two common chemotherapeutic regimens on the basis of Cathepsin D levels. Setting: The present research was carried out in the department of Oncology, Sir Ganga Ram Hospital and INMOL Hospital Lahore. Materials & methods: A total of 50 female patients with breast cancer were included in this study. Patients were divided into two groups. Each group consisted 25 patients. Each group received either TAC or FAC chemotherapy regimen. Blood levels of Cathepsin D were compared between each group. Results: Data was analyzed on the basis of their age, socioeconomic status, family history, menstrual history, use of contraceptives & body mass index. Cathepsin D levels were analyzed prior, mid & post treatment using two chemotherapy regimens. Conclusion: Both chemotherapy regimens i.e TAC & FAC are clinically effective. Although TAC therapy has reduced the level of Cathepsin D more as compared to FAC therapy which suggests regimen TAC is more effective in the treatment of breast cancer.